Faktor-Faktor yang Memengaruhi Daya Saing Industri Unggas Ayam Kampung (Studi Kasus PT Dwi dan Rachmat Farm, Bogor) - Siti Aedah; MH Bintoro Djoefrie; Gendut Suprayitno (Institut Pertanian Bogor, 2016)
The poultry industry in Indonesia often experience ups and downs the last few years. The volatility of broiler effort to shocks opportunities to develop local businesses like poultry chicken that is currently growing in popularity compared with other poultry meat. Chicken poultry industry is highly prospective, given the need for animal protein derived from poultry meat is increasing and is supported by the rapid development of the culinary industry today. The purpose of this study to identify the factors affecting the competitiveness of the poultry industry chicken. Descriptive research method, processed and analyzed using the Porter Diamond Model. The results showed the factors that influence competitiveness the poultry industry kampong chicken which has the highest attribute values, namely: human resources, the number of buyers and buyer growth rate, breeding, industrial replacement products, roadmap and business plan development of chicken, a conducive business climate. Attributes of the lowest infrastructure, capital resources, integration of industry suppliers and facilitation of exports.